Biological treatment and exercise as an alternative to typical rheumatoid arthritis therapy: pathophysiology and effects - Aghadi, Artur; Brzuszkiewicz, Kinga; Dybała, Ewelina; Cuber, Iwona; Mazurek, Magdalena; Białowąs, Edyta; Piekarska, Małgorzata; Kasperski, Radosław (Journal of Education, Health and Sport, 2023)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease of unknown etiology that mainly affects the joints, but extra-articular symptoms may also occur. The global prevalence of RA is approximately 5 cases per 1,000 adults[1]. A better understanding of the pathophysiology of the disease in the treatment of RA has led to the development of more effective treatments. Current drugs include glucocorticoids (GCs) and synthetic and biological disease-modifying anti-rheumatic drugs (DMARDs). Apart from these, the most commonly used analgesics are non-steroidal anti-inflammatory drugs (NSAIDs). BLMPs work by targeting specific molecules involved in the inflammatory process, not just symptom relief. Purpose: To review the currently available PubMed data on biologics and exercise for RA and their mechanisms in the context of disease pathophysiology and future prospects. Brief description of the state of knowledge: BLMPs are a necessary alternative in patients who have not achieved the treatment goal for 6 months or have experienced side effects during treatment with conventional disease-modifying drugs. We also analyzed the effect of exercise on the course of RA. Conclusions: The introduction of bDMARDs has opened a new era in the treatment of diseases such as RA. However, due to the difficult access to this form of therapy, side effects, contraindications to currently used drugs, and increasingly well-known mechanisms, there is also a need to constantly search for new solutions. A growing body of evidence in recent years suggests that regular physical activity has a positive effect on various aspects of RA, including disease-related outcomes, mental well-being, and cardiovascular health. Also in this non-pharmacological field, further research is needed to fully understand the mechanisms behind these effects.